Hubungan antara Faktor Risiko dan Tingkah Laku Pengguna terhadap Pembelian Secara atas Talian - Ab Rahman, Nurul Asyikin; Abu Seman, Noor Aslinda (Research in Management of Technology and Business, 2020)
The rapid growth of the internet has also changed the lifestyle of the community in purchasing and online purchase methods are becoming increasingly popular. Most of the factors examined by previous studies have shown a positive factor in influencing online purchases. However, consumers are still showing a negative perception of risk factors such as shipping risk, financial risk, security risk, product risk and time risk in making online purchases. Therefore, this study is conducted to examine the relationship between risk factors and consumer behavior in online purchases. A quantitative approach with cross sectional design was used in this study. A total of 234 respondents were UTHM students involved in this study. The findings show that there is a high level of risk factor in making online purchases. In addition, there is some positive and negative relationship between risk factors and consumer behavior in making online purchases. Hence, different approaches and ways should be made by the trader to convince the buyer and reduce the risk that the buyer is concerned about making online purchases.